Understanding the long-term impact of an overseas immersion programme on pre-service teachers' learning to teach: a Hong Kong case. Issue 1 (2nd January 2022) - Yu, Baohua; Ding, Feng; Yuan, Rui Eric
ABSTRACT: The present study seeks to explore the long-term impact of an overseas immersion programme on pre-service teachers' professional learning in Hong Kong. In-depth interviews with 11 pre-service teachers about their immersion experiences and post-immersion learning revealed their professional gains and challenges brought by their exposure to different cultures and educational systems in foreign countries. In particular, they reported on the sustained influences of immersion on their cultural awareness and pedagogical thinking in their current classroom teaching practice. The paper concludes with suggestions for the improvement of immersion programmes as an important component of current pre-service teacher education.